As bruxas e as indígenas Tupinambás em imagens: o papel da imprensa na criação de estereótipos durante o século XVI - Couto, Beatriz Nogueira (2024)
In this dissertation we aim to discuss how the persecution of the Catholic Church associated with the dissemination of images of the Tupinambá indigenous people influenced the dissemination of stereotypes of women seen as witches in pamphlets in Europe in the 16th century. The witch hunt was one of the greatest genocides in modern history. During this period, thousands of people were persecuted, tortured and killed, especially women. Considered inferior beings, they were considered more prone to the influences of the Devil, and, therefore, to witchcraft. At the time, the press saw that witchcraft and the supernatural were profitable subjects; pamphlets with these themes circulated with short headlines, simple texts and woodcuts that caught the population's attention. Woodcuts developed to develop stereotypes of the image of women as seductresses and more, while at the same time they were essential in shaping the imagery of the Christian West. In this context, images of indigenous Tupinambá cannibals also circulated intensely in Europe after the arrival of Europeans in the Americas. The anthropophagic ritual of the indigenous people was represented there in pamphlets associated with the witches' tendency to vices. For this work, we used as a tool for analyzing the complex thought of Edgar Morin, the way of understanding the images of Norval Baitello Junior, Hans Belting and Isabelle Anchieta, as well as other authors such as Silvia Federici and Peter Burke to understand Europe in the 16th century and the stereotypes present in the construction of the image of the witch